2018
DOI: 10.1093/jcr/ucy057
|View full text |Cite
|
Sign up to set email alerts
|

Slider Scale or Text Box: How Response Format Shapes Responses

Abstract: Consumer payments elicited on slider scales can be systematically different from those elicited through text boxes because of the end point assimilation effect. When people use text boxes to make payments, they evaluate monetary values relative to the starting point of the response range. In contrast, when people use slider scales, they evaluate monetary values relative to the starting point as well as the end point of the response range. Consequently, payments elicited on slider scales tend to be assimilated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Evidence based dietary guidelines, advice, and policy encourages people toward sustainable and healthy diets (Kause et al, 2009; Health Council of the Netherlands, 2011; Ministers NC, 2014;Reynolds et al, 2014;Monteiro et al, 2015;Fischer and Garnett, 2016;Freidberg, 2016;van't Veer et al, 2017;Poore and Nemecek, 2018;CCC, 2020). However, recent research suggests there is a food-knowledge disconnect between the food research community, and the general public, with the citizens typically underestimating the carbon footprint, misestimating portion sizes, and energy content of foods (Rolls et al, 2002;Choi and Pak, 2006;Carels et al, 2007;Steenhuis and Vermeer, 2009;Chernev and Chandon, 2010;Miyazaki et al, 2011;Lee et al, 2012;Holmstrup et al, 2013;Cohen and Story, 2014;Liu et al, 2015;Jones et al, 2016;Panzone et al, 2016, in press;Hartmann and Siegrist, 2017;Edelson et al, 2018;Shi et al, 2018;Camilleri et al, 2019;Kemper et al, 2019;Thomas and Kyung, 2019). The public are motivated to reduce the environmental impact of their diet with two thirds of surveyed EU consumers being open to changes in diet and 40% having already reduced or stopped red meat consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence based dietary guidelines, advice, and policy encourages people toward sustainable and healthy diets (Kause et al, 2009; Health Council of the Netherlands, 2011; Ministers NC, 2014;Reynolds et al, 2014;Monteiro et al, 2015;Fischer and Garnett, 2016;Freidberg, 2016;van't Veer et al, 2017;Poore and Nemecek, 2018;CCC, 2020). However, recent research suggests there is a food-knowledge disconnect between the food research community, and the general public, with the citizens typically underestimating the carbon footprint, misestimating portion sizes, and energy content of foods (Rolls et al, 2002;Choi and Pak, 2006;Carels et al, 2007;Steenhuis and Vermeer, 2009;Chernev and Chandon, 2010;Miyazaki et al, 2011;Lee et al, 2012;Holmstrup et al, 2013;Cohen and Story, 2014;Liu et al, 2015;Jones et al, 2016;Panzone et al, 2016, in press;Hartmann and Siegrist, 2017;Edelson et al, 2018;Shi et al, 2018;Camilleri et al, 2019;Kemper et al, 2019;Thomas and Kyung, 2019). The public are motivated to reduce the environmental impact of their diet with two thirds of surveyed EU consumers being open to changes in diet and 40% having already reduced or stopped red meat consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison of input methods on selfreport drinking behavior found that responses using a slider were inflated compared to those input using a text box (Kemper et al, 2019), however it is not clear whether this effect will be present in measures related to perceptions of energy content and carbon footprint. As input method can impact participant response (Kemper et al, 2019;Thomas and Kyung, 2019), it is important to identify the most appropriate input method to gauge an accurate understanding of carbon footprint and energy content knowledge of citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Janiszewski & Uy, 2008; Northcraft & Neale, 1987;Pan & Thomas, 2022;Thomas & Kyung, 2019 Price fairness judgments: Is the price unfair? When people use this decision rule, they make a purchase decision by judging whether the price is fair or unfair.…”
Section: Decision Rulementioning
confidence: 99%
“…Because our dependent variable, Donation, is discrete and bounded at zero and follows a Poisson distribution, we used a Poisson regression to estimate the effect of the conditions on Donation (see also Thomas and Kyung 2019):…”
Section: Model Specificationmentioning
confidence: 99%